Healthy Lifestyle Of Students In The Educational Process By Means Of Adaptive Physical Culture - Asatillaevich, Abbasov Bakhadir (Indonesian Journal Publisher, 2024)
To develop, theoretically substantiate and experimentally verify the pedagogical conditions for the formation of a healthy lifestyle among university students using adaptive physical culture.